The arrival of Grey : a re-evaluation of George Grey's governance at the Cape of Good Hope, 1854-1861 - Keegan, Thomas (Department of Historical Studies, 2016)
This dissertation studies the period of George Grey's governance at the Cape from 1854 to 1861. This is examined as a period in which change in British administration impacted imperial policy pertaining to the Cape. The relationships between Cape governors, particularly George Grey, and successive British administrations has received inadequate attention. When Grey first arrived, he was allowed a great degree of freedom by Whig politicians; this had changed by the end of his appointment, when Conservatives had come into power. During this period the granting of greater constitutional independence to settler populations across the British Empire was being undertaken and this led to misunderstandings and conflicts over colonial governors' functions and responsibilities. In this context, Grey himself is an object of study. Numerous historical portrayals define him as a figure of great historiographical interest and dispute. Arguments about Grey often revolve around his treatment of native peoples. Engaging this, I attempt to compare and contrast his representations of different native peoples, particularly the Maori and the Xhosa, discussing why such differences may have existed. This dissertation defines this period as one of scientific growth at the Cape, and Grey's influence in promoting the growth of a self--‐conscious public sphere in colonial society is thus investigated. As the Cattle-Killing holds a prominent place within various Cape histories, historiographical examination of this event has taken place. The Cape populations' reactions to Grey's policies have been examined. Suggestions are made that Cape 'victory' over the Xhosa, following the Cattle-Killing, coincided with this growth in scientific endeavour in promoting the place of the Cape in the 'civilised' British colonial order.